Medición y evaluación en comunicación estratégica. Caso de estudio Campaña Permanente de Educación en Seguridad Vial del Fondo de Accidentes de Tránsito FONSAT - Tapia Escalante, Mercedes del Cisne (2014)
In this thesis, we study the Permanent Road Safety Education Campaign of the Road Accident Fund FONSAT, implemented from May to November 2013 to carry out the measurement and evaluation in strategic communication, in order to prove that the strategic communication planning, including the role of measurement and evaluation of results, allow us to determine the contribution of communication to manage objectives of public or private entities. To achieve this purpose we used the model of measurement and evaluation in strategic communication, "Communication Management Bridge,” which will be applied using a qualitative methodology through research based on interviews, observable behaviors, and documents obtained from FONSAT, to attain exploratory and descriptive data to meet the objectives for the case study. The application of this study is to demonstrate that not only is it important to manage communication activities, but to measure and evaluate them as well in order to see the effects they have on the target audiences.